Factors Affecting Student Learning Motivation During the Covid-19 Pandemic - Ebnovrio Hanesty; Neviyarni Neviyarni; Yeni Karneli (Universitas Negeri Padang, 2020)
The last few years have been the most difficult due to Covid-19, a disease that attacks and is transmitted through the human respiratory tract, sweeping the world. As a result, a number of public facilities were closed including schools so that the distance learning model was applied. The condition of the Covid-19 pandemic has made it possible to decrease student learning motivation which is the key to student learning success. Thus, it is important to study the factors that affect student learning motivation. This study aims to describe student learning motivation in terms of self-concept support, parental support, subject teachers, guidance and counseling teachers and smartphone facility factors. This type of research is descriptive using quantative methods. The population of this study were students of MTsN 2 Pesisir Selatan, totaling 711 students, with a sample of 256 students who were taken using a proportional stratified random sampling technique. The results of the study found that in general the learning motivation of MTsN 2 Pesisir Selatan students during the Covid-19 pandemic was in the moderate category, which means that most students lost their motivation to learn.